Usefulness of K-means Method in Detection Corporate Crisis - Joanna Dyczkowska (European Financial and Accounting Journal, 2010)
Market situation and business environment of construction companies influence significantly decisions met by this group of entities. These decisions are reflected in financial statements, later on. The evaluation of financial condition, which aims at diagnosing corporate crisis, must not disregard a market situation. Taking this assumption into account a classification of publicly quoted construction companies using k-means method was conducted. This procedure enabled to divide the examined sample into five clusters of companies characterized by `the best', `good', `acceptable', `weak' and `the poorest' financial condition. The application of the aforementioned algorithm helped also to determine levels of financial ratios typical for each cluster. This kind of analytical approach is particularly useful for investors, since it informs how particular companies perform in comparison to their competitors.
Keywords: G32; G33; M41; 650; Numerical taxonomy; Cluster analysis; K-means method; Financial situation; Current ratio; Average collection period; Return on sales ratio; Liabilities payment time; Assets turnover; Return on assets